Bombers - Dartford, Mark and kevin Doyle (London Angus, 2004)
Discusses the military use of aircraft to drop bombs and describes the development of particular kinds of bombers.
Include Index.
Keywords: Bombers -- Juvenile Literature. -- Bombers. -- Airplanes, Military